The Impact of Work-Life Balance on Alleviating Work Stress and Enhancing Employee Productivity in the Hotel Industry - Hernawani Bidaya; Dyah Palupiningtyas (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
This study aims to analyze the role of work-life balance in reducing work stress and improving hotel employee productivity in Semarang Regency. Using a quantitative approach and explanatory research design, the study involved 271 hotel employees selected through proportionate stratified random sampling. Data were collected using questionnaires and analyzed using path analysis with AMOS 26. The results showed that work-life balance had a significant negative effect on work stress (β = -0.542, p < 0.01) and a significant positive effect on work productivity (β = 0.384, p < 0.01). Work stress was proven to partially mediate the relationship between work-life balance and work productivity, with a mediation proportion of 39.6% confirmed through the Sobel test (z = 4.876, p < 0.01). These findings imply the importance of developing policies and programs that support hotel employees' work-life balance to increase productivity through reduced work stress levels.